Pembelajaran Mufradat dalam Meningkatkan Maharah Al-kalam Peserta Didik SDIT Nurul Kautsar Makassar - Surya, Nurelita; Kasim, Amrah; Arsyad, Aisyah (Shaut al Arabiyyah, 2026)
This research aims to analyze the Mufradat learning process in improving the maharah al-kalam of SDIT Nurul Kautsar Makassar students. This type of research is descriptive qualitative with a Grounded Theory research approach and analyzes improvements using an oral test evaluation approach. The results of this research show that the mufradt learning process obtained by the results of the interviews showed an increase in students' maharah al-kalam in the medium category and the oral test on students showed that 25% of students got high scores, the students who got 41.6% had medium scores, 16% of students with low scores and 16% of students who got very low scores. The implication of this research is that serious persistence and attention is needed from all parties, especially Arabic language teachers. For this reason, it is recommended that Arabic language teachers increase their attention and efforts in motivating students and find solutions such as further developing teaching methods so that they are interested in learning Arabic, and even foster in students a need for Arabic.